Fuzzy controlled modified reduced switch converter for switched reluctance motor under dynamic loading - Ritika Asati; Deepak S. Bankar; Aishwarya Apte; Amit L. Nehete; Yogesh Mandake (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
In this paper, modified reduced switch converter topology is used to drive 8/6 pole, 7500 W switched reluctance motor (SRM) with an electric vehicle (EV) load. Fuzzy logic control (FLC) is developed for the modified converter topology and its performance is compared with the proportional integral (PI) controller. Analytical equations, switching pulses and different mode of operation are presented for modified reduced switch converter using double phase magnetization scheme. The converter topology adopts a modified switching sequence i.e., magnetization then freewheeling before demagnetization. It offers lesser torque ripples, reduced phase current and need only four switches for a 4-phase SRM drive. Modified reduced switch converter is simulated in MATLAB-simulation to investigate and compare the steady state waveforms and transient speed response of the PI and FLC. Torque ripple in modified converter is 50% less than the classical converter. Peak overshoot and settling time performance of FLC is superior as compared to PI, when applied to modified converter with EV loading.